1997
DOI: 10.3904/kjim.1997.12.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Primary T-cell Lymphoma of the Colon

Abstract: A 40-year-old woman had been diagnosed with Crohns disease in September 1994, but later examinations revealed a primary T-cell lymphoma of the colon. Colonoscopic and histological examination showed ulcerative lesions simulating Crohns disease involving the entire colon and the terminal ileum, and she was first diagnosed as having Crohns disease. Differential therapeutic strategies, including corticosteroid, had improved the symptoms which were dominated by abdominal pain. When she visited our institute in Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Previous studies in the West have shown that almost all cases of primary colorectal lymphoma are derived from B cells (6,7). However, primary colorectal lymphomas of T-cell origin have been reported in Eastern countries (8)(9)(10)(11)(12). According to a recent study from Taiwan (11), the proportion of T-cell lymphomas was as high as 42% in the East.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the West have shown that almost all cases of primary colorectal lymphoma are derived from B cells (6,7). However, primary colorectal lymphomas of T-cell origin have been reported in Eastern countries (8)(9)(10)(11)(12). According to a recent study from Taiwan (11), the proportion of T-cell lymphomas was as high as 42% in the East.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is the commonest site of extranodal lymphoma,29 with colorectal lymphomas comprising between 10% and 20% of primary gut lymphomas in larger published series 3031 Several reports of primary intestinal lymphoma masquerading as IBD have been described,32 33 including a patient with ileocolonic T cell lymphoma, originally thought to be Crohn's disease at colonoscopy, whose symptoms initially improved on corticosteroids before the correct diagnosis was made nine months later 34…”
Section: Discussionmentioning
confidence: 99%
“…A case of intestinal T-cell lymphoma involving the rectum was previously reported in Korea6). However, although the T-cell markers were expressed, the exact subtype was not defined and whether the patient was non-AIDS or not was not clearly mentioned in that case.…”
Section: Discussionmentioning
confidence: 99%